2021
DOI: 10.3390/pathogens11010002
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Toxoplasma gondii in Asian Elephants (Elephas maximus indicus) in Thailand

Abstract: Toxoplasma gondii is the causative agent of toxoplasmosis in humans and various animal species worldwide. In Thailand, seroprevalence studies on T. gondii have focused on domestic animals, and information on infections in Asian elephants (Elephas maximus indicus) is scarce. This study was conducted to determine the seroprevalence of T. gondii infection in archival sera collected from 268 elephants living in Thailand. The serum samples were analyzed for anti-T. gondii immunoglobulin G antibodies using the latex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 37 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…Toxoplasmosis is a disease caused by Toxoplasma gondii and occurs widely in animals and humans [28,39,87,88]. In humans, the infection results in a range of signs and symptoms, including gastrointestinal, malaise, anorexia, weight loss, pain, fever, systemic disease, or death, and transmission is characteristically fecal-oral, through contaminated soil, or fomites [28,39,87,88]. In elephants, individuals may be asymptomatic carriers, but infection may result in debilitating gastrointestinal and systemic disease conditions [125].…”
Section: Toxoplasmosismentioning
confidence: 99%
See 1 more Smart Citation
“…Toxoplasmosis is a disease caused by Toxoplasma gondii and occurs widely in animals and humans [28,39,87,88]. In humans, the infection results in a range of signs and symptoms, including gastrointestinal, malaise, anorexia, weight loss, pain, fever, systemic disease, or death, and transmission is characteristically fecal-oral, through contaminated soil, or fomites [28,39,87,88]. In elephants, individuals may be asymptomatic carriers, but infection may result in debilitating gastrointestinal and systemic disease conditions [125].…”
Section: Toxoplasmosismentioning
confidence: 99%
“…Relatively little is known regarding disease incidence or prevalence [23,32], although one study found antibodies in 45.5% of Asian elephants, indicating that animals had, at some point, been exposed to the pathogen [125]. Another study also showed widespread exposure but with no determination regarding the source of infection [39].…”
Section: Toxoplasmosismentioning
confidence: 99%